The first Ichneumonid fossil from the Early Pleistocene of Madeira Island (Portugal) - Góis-Marques, Carlos A.; Jesus, José; de Sequeira, Miguel Menezes; Madeira, José (Zootaxa, 2019)
In oceanic islands, well age-constrained deposits containing arthropod somatofossils (body fossils) are rare. However, when available, these are important for providing empirical and independent minimum ages for molecular phylogenetic dating and complementary data on taxonomy, evolution and palaeobiogeography information of the biological groups found as fossils. This is especially important for taxa that speciated within oceanic islands, many becoming single island endemics (SIE). Recently, associated with a 1.3 Ma (Calabrian) fluvial and lacustrine sedimentary deposit from Porto da Cruz in Madeira Island (Fig. 1), a wing, putatively identified as Hymenoptera, was found. Here we describe this wing fossil as belonging to Ichneumonidae, a group with ca. 30% of SIE in Madeira Island. Moreover, this is the first somatofossil of ichneumonid parasitic wasps found in Madeira Island and in Macaronesian islands (i.e. Azores, Madeira, Canaries and Cabo Verde).